SISTEM PENUNJANG KEPUTUSAN PENERIMAAN KARYAWAN MENGGUNAKAN METODE SMART - Vera Tjandra; Marlina; Syaiful Rahman (KHARISMA Tech, 2018)
The purpose of this research is to build a Decision Support System that can assist the acceptance of employees based on the criteria and parameters that have been determined by the CV. Tri Tunggal Sejati. The method used in the process of data collection is the interview of the CV. Tri Tunggal Sejati. The SPK method used is Simple Multi Attribute Rating Technique (SMART). In this study the criteria used are experience, education, age, microsoft office test, responsible, analyze the problem, make decisions, achievement tests, personality tests and intelligence tests and each criteria has parameters according to the criteria and parameters the company desires. From the results of this study produced a SPK design that can help the CV. Tri Tunggal Sejati in employee acceptance. Final decision making remains in the hands of the CV. Tri Tunggal Sejati, and the system only provides an alternative choice that makes it easy in decision making.